Python GUI Programming with Tkinter : Develop responsive and powerful GUI applications with Tkinter. - Moore, Alan D. (Packt Publishing, 2018)
Tkinter is a lightweight, portable, and easy-to-use graphical toolkit available in the Python Standard Library. Due to its simplicity and availability, it is widely used to build GUIs in Python. This book teaches how to design and build a functional, appealing, and user-friendly GUI using one of the most powerful languages: Python with Tkinter.